Effect of endogenous androgens on 17β-estradiol-mediated protection after spinal cord injury in male rats - Supatra Kachadroka (2018)
Several groups have recently shown that 17β-estradiol is protective in spinal cord injury (SCI). Testosterone can be aromatized to 17β-estradiol and may increase estrogen-mediated protection. Alternatively, testosterone has been shown to increase excitotoxicity in models of central nervous system (CNS) injury. These experiments test the hypothesis that endogenous testosterone in male rats alters 17β-estradiol-mediated protection by evaluating a delayed administration over a clinically relevant dose range and manipulating testicular-derived testosterone. Adult male Sprague Dawley rats were either gonadectomized or left gonad-intact prior to SCI. SCI was produced by a midthoracic crush injury. At 30min post SCI, animals received a subcutaneous pellet of 0.0, 0.05, 0.5, or 5.0mg of 17β-estradiol, released over 21 days. Hindlimb locomotion was analyzed weekly in the open field. Spinal cords were collected and analyzed for cell death, expression of Bcl-family proteins, and white-matter sparing. Post-SCI administration of the 0.5- or 5.0-mg pellet improved hindlimb locomotion, reduced urinary bladder size, increased neuronal survival, reduced apoptosis, improved the Bax/Bcl-xL protein ratio, and increased white-matter sparing. In the absence of endogenous testicular-derived androgens, SCI induced greater apoptosis, yet 17β-estradiol administration reduced apoptosis to the same extent in gonadectomized and gonad-intact male rats. These data suggest that delayed post-SCI administration of a clinically relevant dose of 17β-estradiol is protective in male rats, and endogenous androgens do not alter estrogen-mediated protection. These data suggest that 17β-estradiol is an effective therapeutic intervention for reducing secondary damage after SCI in males, which could be readily translated to clinical trials. © 2010, Mary Ann Liebert, Inc.